Weighted block Runge-Kutta method for solving stiff ODEs - Aksah, Sauﬁanim Jana; Ibrahim, Zarina Bibi; Rahim, Yong Faezah; Ibrahim, Siti Nur Iqmal (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this paper, weighted block Runge-Kutta (WBRK) method is derived for solving stiff ordinary differential equations (ODEs). Implementation of weights on the method and its stability region are shown. Numerical results of the WBRK method are presented and compared with the existing methods to prove the ability of the proposed method to solve stiff ODEs. The results show that the WBRK method has better accuracy than the comparing methods.